Could scoring tailed and dumbbell-shaped nuclei increase the sensitivity of micronucleus analysis as a biomarker of radiation exposure? - Dwi Ramadhani; Arum Wulansari; Viria Agesti Suvifan; Isnaini Farida; Wiwin Mailana; Hartini Ahadiyatur Ru’yi; Syarifatul Ulya; Sofiati Purnami; Mukh Syaifudin (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2021)
In the cytokinesis-block micronucleus (CBMN) assay, micronuclei (MNi), nucleoplasmic bridges (NPBs), and nuclear budding (NBUD) are the most commonly analysed morphological types of nuclear abnormalities. In contrast, tailed and dumbbell-shaped nucleus have historically received little attention in the CBMN assay. Interestingly, the incidence of tailed and dumbbell-shaped nuclei in lymphocytes is closely related with that of dicentric chromosomes or NPBs in the CBMN assay. To provide a better picture of the implications and significance of tailed and dumbbell-shaped nuclei as markers of radiation exposure, a literature review was performed in this study. Twenty articles were found in PubMed, PubMed Central, and manually searched. The articles were screened and those that met the inclusion criteria and did not meet the exclusion criteria were reviewed by all authors. At the end, nine articles were included. In conclusion, the assessment of in vivo tailed nuclei in blood smears and accounting for the occurrence of dumbbell-shaped nuclei in the CBMN assay can increase the sensitivity of the CBMN assay for biodosimetry involving a high dose exposure.